Comparing and quantifying the ecological niches of the saltmarsh grass Spartina alterniflora and major mangrove species in China - Cui, Lina; Qiu, Jianwei; Berger, Uta; Cao, Minmin; Li, Weiyang; Jiang, Jiang (Scientific reports, 2025)
The concept of niche similarity is crucial for understanding species invasions. An in-depth understanding of different niches can aid in developing effective control strategies, not only at the community level but also in population interactions. In this study, we investigated the invasion of Spartina alterniflora in China by selecting nine major mangrove species along the Chinese coast. Utilizing an ensemble species distribution model (ESDM), we compared the niche characteristics of these mangroves with S. alterniflora . We found that S. alterniflora has a broad latitudinal adaptability (39.22–21.67˚N), significantly greater than the mangroves. Excoecaria agallocha has the largest potential distribution area (74,729 km 2 ), while Kandelia obovata shows the widest climatic adaptability (latitude: 30.85˚N to 18.19˚N). The ecological niches of the mangroves and S. alterniflora overlap (D.overlap: 0.015–0.254, Niche similarity index: 0.044–0.551), driven by different species-specific factors. K. obovata and S. alterniflora have the highest niche similarity due to the similarities in precipitation during the driest month and precipitation seasonality. Overall, mangroves in China are vulnerable to invasion by S. alterniflora . Strengthening mangrove protection is essential for their healthy development, especially under frequent extreme weather conditions, with a focus on protecting K. obovata .